2021
DOI: 10.1080/02601370.2021.1919768
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits from non-formal digital training sessions in later life: views of older adult learners, peer tutors, and teachers

Abstract: Rapid development of digital technologies affects the lives of all people and often leads to people being in unequal positions regarding digital skills training opportunities. Older adults' motivations for learning digital skills vary, but they are generally connected with expectations of upcoming benefits. This study investigates the self-perceived benefits of older adults, information and communications technology (ICT) teachers and peer tutors who have participated in digital training sessions in olderadult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 58 publications
1
24
0
1
Order By: Relevance
“…On the other hand, there were also older adults who already had the skills to use digital services and devices, and who were eager to learn more and to improve their digital literacy skills. Therefore, it is crucial that the support given to older adults to learn digital literacy skills and the appropriation of new technology is carefully planned and implemented in a way that considers older adults’ needs and their reasons for seeking guidance [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there were also older adults who already had the skills to use digital services and devices, and who were eager to learn more and to improve their digital literacy skills. Therefore, it is crucial that the support given to older adults to learn digital literacy skills and the appropriation of new technology is carefully planned and implemented in a way that considers older adults’ needs and their reasons for seeking guidance [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…ICTs facilitate social connectivity and can help reduce social isolation, allowing older adults to feel less lonely by increased online interactions and connections with others [ 27 ]. Studies have reported the benefits of digital training and adoption in older adults to mitigate the adverse effects of social and spatial barriers and enhance social connections, curb isolation and promote a better quality of life [ 28 , 29 , 30 ]. We must not underestimate that self-efficacy and motivation, especially when learning and using ICTs, can bring in many immediate benefits, in addition to family communication and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Authors in the field argue that when students were able to check their own results and correct their own procedures, they became more independent from a pedagogical perspective, increasing their autonomy and requiring less support from their teachers or instructors [78][79][80]. The fact that students could associate different mathematical concepts in a more complex way is rational considering that these associations were promoted in three ways (teacher's explanations, peer's help, and analytical and graphical developments of the digital tools) instead of just the one way (teacher's explanations) of traditional learning [81][82][83][84]. Finally, the fact that students in the experimental group did more exercises and problems than those in the control group may be attributable to two main factors: the helping behaviour that usually arises during peer tutoring interactions [85][86][87][88] and the instant feedback provided by the digital tools [89][90][91].…”
Section: Discussion For Research Question 2: Effects On Way Students ...mentioning
confidence: 99%